1999
DOI: 10.1093/0198269943.001.0001
|View full text |Cite
|
Sign up to set email alerts
|

German and Scandinavian Protestantism 1700-1918

Abstract: This book is the first history in English of the Lutheran Church in Germany and Scandinavia in the eighteenth and nineteenth centuries. Beginning and ending in war, this period was of particular unease and upheaval for the Church. Attempts to emulate the spiritual community of the early Church, reform of the Church establishment and steps taken to enlighten parishioners were almost always held back by the anomalous structural legacy of the Reformation, tradition and parish habit, sacred and profane. The birth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…"3 These claims were rooted in an unabashedly Whig reading of the history of religious toleration that started with the radicals of the Reformation era and culminated in religious pluralism, freedom of conscience, and separation of church and state in modern America. However, in the last half century the Anabaptists have lost their prominence in historical writing on toleration, and in a recent a growing interest in the seventeenth-century history of Anabaptism, have encouraged research in this area: see, for example, Troy Osborne, "The Development of a Transnational 'Mennonite' Identity among Swiss Brethren and Dutch Doopsgezinden in the Sixteenth and Seventeenth Centuries," Mennonite Quarterly Review 88 (2014): 195-218; John Roth, "Marpeck and the Later Swiss Brethren, 1540-1700," in A Companion to Anabaptism and Spiritualism, 1521-1700, ed. John D. Roth and James M. Stayer (Leiden: Brill, 2007, 347-88, here at 385-86; and Astrid von Schlachta, Gefahr oder Segen?…”
Section: Geoffrey Dipplementioning
confidence: 99%
See 3 more Smart Citations
“…"3 These claims were rooted in an unabashedly Whig reading of the history of religious toleration that started with the radicals of the Reformation era and culminated in religious pluralism, freedom of conscience, and separation of church and state in modern America. However, in the last half century the Anabaptists have lost their prominence in historical writing on toleration, and in a recent a growing interest in the seventeenth-century history of Anabaptism, have encouraged research in this area: see, for example, Troy Osborne, "The Development of a Transnational 'Mennonite' Identity among Swiss Brethren and Dutch Doopsgezinden in the Sixteenth and Seventeenth Centuries," Mennonite Quarterly Review 88 (2014): 195-218; John Roth, "Marpeck and the Later Swiss Brethren, 1540-1700," in A Companion to Anabaptism and Spiritualism, 1521-1700, ed. John D. Roth and James M. Stayer (Leiden: Brill, 2007, 347-88, here at 385-86; and Astrid von Schlachta, Gefahr oder Segen?…”
Section: Geoffrey Dipplementioning
confidence: 99%
“…However, there is no indication of who the authors actually were, and the text itself suggests that it is the work of the whole community. See Wälchli, 14-15, 65;Leu and Scheidegger, Zürcher Täufer, 229;and Hanspeter Jecker, Ketzer-Rebellen-Heilige: Das Basler Täufertum von 1580-1700(Liestal: Verlag des Kantons Basel-Landschaft, 1998, 445. 18 Wälchli,14.…”
Section: Geoffrey Dipplementioning
confidence: 99%
See 2 more Smart Citations
“…31 Hope calls the boundary between the Pietists and Herrnhutists blurred if not non-existent, and one must agree. 32 In 1743, the Herrnhut movement was banned, 33 although after the tolerance manifesto issued by Catherine the Great in 1764, the Brothers were again allowed to come to Russia, which is why the Brothers in Estonia and Livonia concluded that they had the same rights. 34 The Rationalist movement 35 , which arrived via the pastors who came from foreign universities, was opposed to the "kind-heartedness" of Pietism and Herrnhutism, but it was well-meaning towards them.…”
mentioning
confidence: 99%